1999
DOI: 10.1002/(sici)1099-1719(199911)7:4<165::aid-sd117>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Tourism and sustainable development: an analysis of policy and guidelines for managing provision and consumption

Abstract: This paper reviews some of the literature and guidance provided for businesses considering responses to the environmental aspects and impacts of their tourist activities. It concentrates on the role of individual business organizations within the tourism industry and examines both supply‐side (production) and demand‐side (consumption) policies. In its review of a number of guidelines the paper attempts to make recommendations for improving both the provision of tourism services through supply chain management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(38 citation statements)
references
References 19 publications
1
29
0
1
Order By: Relevance
“…The theories of SSCM start from the principle that in order for companies to ensure that their services and products are sustainable, they need to ascertain whether every component or element of the product or service they buy from their suppliers is sustainable, forcing companies to engage not only in their downstream supply chain towards the consumer, but also their upstream chain towards producers (Lippmann, 1999;Lysons, 1996;Welford et al, 1999). Sustainability is a debated concept, but is here defined as "… living and working in such a way that human society will be possible for generations to come -and translating that into the changes required of an individual organisation -changes which maintain the organisation's capacity for producing human benefits, and including the profitability needed for survival, while optimising the environmental balance of its operations" (Crosbie and Knight, 1995:15).…”
mentioning
confidence: 99%
“…The theories of SSCM start from the principle that in order for companies to ensure that their services and products are sustainable, they need to ascertain whether every component or element of the product or service they buy from their suppliers is sustainable, forcing companies to engage not only in their downstream supply chain towards the consumer, but also their upstream chain towards producers (Lippmann, 1999;Lysons, 1996;Welford et al, 1999). Sustainability is a debated concept, but is here defined as "… living and working in such a way that human society will be possible for generations to come -and translating that into the changes required of an individual organisation -changes which maintain the organisation's capacity for producing human benefits, and including the profitability needed for survival, while optimising the environmental balance of its operations" (Crosbie and Knight, 1995:15).…”
mentioning
confidence: 99%
“…However, referred to elaboration on above discussion indicated that sustainable leisure consists of three domains (Kirkbride, 1999;Gladwin, Kennelly, & Krause, 1995;Welford, Ytterhus, & Eligh, 1999;Williams, & Millington, 2004): local consensus, appraisals, and social carrying capacity. In detail, local consensus is a local community in participating in the sustainable leisure management (Hiwasaki, 2003).…”
Section: Literature Reviewmentioning
confidence: 98%
“…Meanwhile, Welford, Ytterhus and Eligh (1999) and Williams and Millington (2004) review some of the literature and guidelines for business from the supply and demand sides, and they advocate both sides of the tourists through education, improve logistics management, and participation. While, Ostrom, Schroeder and Wynne (1993) and Banuri (2009) found a strong correlation between sustainable development and climate change that focuses on five pillars: adaptation, institutional arrangements, financial and technological support, decreased mitigation, and the development of the target country.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nevertheless, Welford et al (1999) stated that tourism business not only saw the side of supply or demand but should also provide a strong signal between these two parts.…”
Section: Introductionmentioning
confidence: 99%